Water marketing by pipes in the East of the Valley of Mexico - Mora Martínez Efraín; Mora Flores José Saturnino; García Sánchez Roberto Carlos; Palerm Viqueira, Jacinta; Sangerman-Jarquín Dora Ma. (Revista Mexicana de Ciencias Agrícolas, 2018)
Given the water restriction in the Valley of Mexico, where population groups do not have access to water distribution networks or access is restricted, a market for water supplied by tank cars (pipes) is generated. The objective was to analyze the marketing and supply chain of the water distributed by pipes in the East of the Valley of Mexico with data obtained in 2017, as well as the participating agents. The direct method of the marketing channel was used following the product since it is extracted from the well, sold to the “piperos”, who transport it and sell it to the final consumer. The owner of a well was interviewed and fifty interviews were conducted with piperos, with the information the costs incurred by each agent, as well as the respective profit margins and rates, were calculated. It was found that the highest absolute margin per m3 is obtained by piperos (52.63) while the pocero is smaller (14.75). However, when weighting the margins for the respective costs, the highest profit rate (1 180%) is obtained by the pocero, while that of the piperos is lower (206%). It is concluded that the water market supplied by pipes is extremely profitable, because it is not a regulated market, and that if public policies were established through regulation, liquid prices could be reduced in favor of consumers.